The role of information and participation in overcoming users’ initial reluctance: a case study of a decentralized wastewater treatment plant - Vila-Tojo, Sergio; Gómez-Román, Cristina; Sabucedo, Jose-Manuel (Frontiers in Psychology, 2024)
Decentralized wastewater treatment systems are a potential solution to the water crisis. However, in addition to advanced technology, successful implementation of these systems requires broad public willingness to use them. This paper presents the results of a three-phase psychosocial intervention with the users of a business building where a decentralized wastewater treatment plant was installed. The intervention, motivated by complaints from users due to their lack of knowledge about the existence of the plant, aimed at understanding and improving users’ perceptions of the building’s decentralized system. In the first phase, we conducted a focus group with a sample of workers (n = 6) to understand their knowledge and perception of the building’s decentralized wastewater treatment system. Once the main obstacles and facilitators were identified, we designed a second phase where a group of employees (n = 46) were exposed to environmental priming to improve attitudes toward the decentralized plant installed in the building. Finally, in the third phase, a bidirectional informative session was proposed, conducted by experts, to another group of workers (n = 25). Findings suggest that implementing specific psychosocial strategies, such as promoting environmental awareness and providing informative sessions, along with incorporating potential users throughout the process, contributes to better acceptance of the decentralized wastewater treatment plant. This work presents a real case in a pilot plant that can serve as a guide for addressing psychosocial resistance in similar projects.